Erythema annulare centrifugum-like eruption associated with pegylated interferon treatment for hepatitis C - Mark Naccarato; Deborah Yoong; Robert Solomon; Mario Ostrowski (PAGEPress Publications, 2013)
Current standard of treatment for chronic hepatitis C virus infection requires the use of pegylated interferon plus ribavirin. Treatment with these two agents has been associated with numerous side effects, which frequently include dermatologic eruptions. We report a cutaneous eruption associated with interferon having clinical presentation of erythema annulare centrifugum. The eruption occurred within days of the first interferon injection and repeatedly flared following subsequent injections. Our patient was able to continue therapy without interruption, while managing the reaction with topical corticosteroid and oral antihistamine. We conclude that this is a benign cutaneous eruption associated with interferon which can be managed without dis- continuing treatment for hepatitis C.